ERECTA Regulates Cell Elongation by Activating Auxin Biosynthesis in Arabidopsis thaliana - Qu, Xiaoya; Zhao, Zhong; Tian, Zhaoxia (Frontiers in Plant Science, 2017)
The ERECTA family genes, ERECTA (ER), ERECTA-LIKE1 (ERL1), and ERECTA-LIKE2 (ERL2), encode leucine-rich repeat receptor-like kinases in Arabidopsis thaliana. Knocking out these three genes can cause severe phenotypes, which indicates that they play significant roles in plant growth and development. However, the molecular mechanism within remains unclear. Here we show that the short hypocotyl phenotypes of er erl1 erl2 mutants are mainly due to the defects of cell elongation rather than the cell division. In contrast, in the ERECTA overexpression transgenic plants, the hypocotyl length is increased with elongated cells. Moreover, we show that the er erl1 erl2 triple mutant contains a low level of auxin, and the expression levels of the key auxin biosynthesis genes are significantly reduced. Consistent with this observation, increasing exogenous or endogenous auxin levels could partially rescue the cell elongation defects of the er erl1 erl2 triple mutant. Therefore, our results provide a molecular basis for auxin mediated ERECTA control of the hypocotyl length in Arabidopsis thaliana.